Enhancing the evaluation of PI3K inhibitors through 3D melanoma models. (21st March 2016) - Shannan, Batool; Chen, Quan; Watters, Andrea; Perego, Michela; Krepler, Clemens; Thombre, Rakhee; Li, Ling; Rajan, Geena; Peterson, Scott; Gimotty, Phyllis A.; Wilson, Melissa; Nathanson, Katherine L.; et al.
Summary: Targeted therapies for mutant BRAF metastatic melanoma are effective but not curative due to acquisition of resistance. PI3K signaling is a common mediator of therapy resistance in melanoma; thus, the need for effective PI3K inhibitors is critical. However, testing PI3K inhibitors in adherent cultures is not always reflective of their potential in vivo. To emphasize this, we compared PI3K inhibitors of different specificity in two‐ and three‐dimensional (2D, 3D) melanoma models and show that drug response predictions gain from evaluation using 3D models. Our results in 3D demonstrate the anti‐invasive potential of PI3K inhibitors and that drugs such as PX‐866 have beneficial activity in physiological models alone and when combined with BRAF inhibition. These assays finally help highlight pathway effectors that could be involved in drug response in different environments (e.g. p4E‐BP1). Our findings show the advantages of 3D melanoma models to enhance our understanding of PI3K inhibitors.